2003
DOI: 10.1038/nm892
|View full text |Cite
|
Sign up to set email alerts
|

Mimicry and autoantibody-mediated neuronal cell signaling in Sydenham chorea

Abstract: Streptococcus pyogenes-induced acute rheumatic fever (ARF) is one of the best examples of postinfectious autoimmunity due to molecular mimicry between host and pathogen. Sydenham chorea is the major neurological manifestation of ARF but its pathogenesis has remained elusive, with no candidate autoantigen or mechanism of pathogenesis described. Chorea monoclonal antibodies showed specificity for mammalian lysoganglioside and N-acetyl-beta-D-glucosamine (GlcNAc), the dominant epitope of the group A streptococcal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
417
2
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 420 publications
(446 citation statements)
references
References 42 publications
16
417
2
11
Order By: Relevance
“…However, a separate study identified a 60 kDa protein isolated from a neuroblastoma cell line and detected by TS patient sera as the human heat shock protein (hsp60) (Hoekstra et al, 2003). Finally, one study indicated that monoclonal antibodies derived from Sydenham's chorea patients recognized neurolipids and invoked Ca 2+ signaling cascades (Kirvan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, a separate study identified a 60 kDa protein isolated from a neuroblastoma cell line and detected by TS patient sera as the human heat shock protein (hsp60) (Hoekstra et al, 2003). Finally, one study indicated that monoclonal antibodies derived from Sydenham's chorea patients recognized neurolipids and invoked Ca 2+ signaling cascades (Kirvan et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Crossreactivity has been found between N-acetyl-glucosamine (a streptococcal antigen) and lysoganglioside (a transmembrane molecule highly enriched in the CNS) using SC monoclonal antibodies. 146 However, it is still unclear how antibodies could cross the blood-brain barrier. The selective permeability of the blood-brain barrier presumably protects the brain from immunological insult.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…M any disturbances in behavior, including paraneoplastic syndromes, movement disorders, schizophrenia, and autism, as well as other neuropsychiatric syndromes, have been associated with the presence of serum Abs with specificity for some, often unidentified, brain antigen (1)(2)(3)(4)(5)(6). Although data suggesting associations among disease states, brain-reactive Abs, and altered neuronal function continue to accumulate, there is no clear understanding of the mechanisms that permit serum Abs to gain access to brain tissue and then to mediate a change in behavior.…”
mentioning
confidence: 99%